Assessment of drinking water related to arsenic and salinity hazard in Patuakhali district, Bangladesh - Biswas, Raman; Roy, Dhiman; Towfiqul Islam, Abu Reza Md.; Rahman, Md.; Ali, Mir (International Journal of Advanced Geosciences, 2014)
The present study was assessed arsenic and salinity hazard of groundwater for drinking purposes in Patuakhali district, Bangladesh. Total 14 deep tube wells were selected randomly for collecting water samples in the study area. PH, arsenic concentration, salinity and temperature of the water samples were measured by in situ field measurement, HANNA portable arsenic tool box, EC meter and thermometer respectively. The result revealed that the average temperature and PH of the study area were 27°C and 7.09 shows within the permissible limit according to WHO standard. The EC value was ranged from 520 to 1036.66 ? S/cm with an average value of 687.66 ? S/cm was falling within the drinking water quality DOE and WHO standard. The TDS values were ranged from 332.8-363.4 mg/l indicates that all the values are within the ranges for drinking purposes. The study was also shown that arsenic of the ground water samples were ranged between 0 to 335 ppb which are within permissible limit according to Bangladesh Arsenic Standard (BAS). Therefore, it can be concluded that the groundwater is slight to moderate suitable for drinking purposes in terms of arsenic and salinity hazards within the acceptable ranges. It is recommended that groundwater of the study area is good for health. Keywords: Salinity Hazard, Suitability, Deep Tube Wells and Drinking Standard.